SOCIAL AND BUREAUCRATIC PROBLEMS IN SOCIAL POLICY IMPLEMENTATION IN INDONESIA: A STUDY ON THE PROGRAM KELUARGA HARAPAN (PKH) - Wimmy Haliim; Dano Purba (Universitas Kadiri, 2023)
Indonesian Goverment is required to have social policies in reducing poverty, one of which is through the Program Keluarga Harapan (PKH). In fact, some individuals abused their authority in this program. PKH Facilitators commit corruption (bureaucratic pathology) and consumptive behavior (social pathology) shown by PKH beneficiaries. Qualitative research methods and literature studies were used to see the many social and bureaucratic problems in PKH implementation. So that researchers can describe and examine why these problems occur. Using social exchange theory, this article discusses the social problems faced by PKH beneficiaries. As a result, their consumptive behavior occurs because the evaluation process is not optimal from the PKH assistants. So they can abuse the social assistance. The debt bondage they face is also a complex problem. Next, the factors that cause PKH assistants to commit corruption. The complexity of political power relations, bureaucracy and their mentality problems are the dominant factors. The key to this problem lies with the PKH assistants. If they can carry out their role properly, PKH beneficiaries are also subject to every existing regulation. The state must also ensure the professionalism and welfare of PKH assistants to prevent them from committing corruption again.